Catfish Advances, Technology, Experiments - Atamanalp, Muhammed (IntechOpen, 2022)
Catfish, one of the largest groups of freshwater fishes, are not only important ornamentals and sport fishing and research animals but also an important source of protein. This book compiles current research on this species, providing information on its production methods and uses.